Bakar Batu sebagai Alat Diplomasi Politik dalam Membangun Hubungan Antara Pemerintah dan Masyarakat Adat di Kabupaten Jayawijaya - Ahmad Ahmad; Tati Haryati; Irma Paundanan (Jayapangus Press, 2026)
This study examines the role of the Bakar Batu tradition as a model of political diplomacy based on local cultural values between the government and indigenous communities in Jayawijaya Regency, Papua Pegunungan. Using a qualitative descriptive method with a case study and political ethnography approach, the research involved seven key informants consisting of traditional leaders, religious figures, government officials, political actors, representatives of the Indigenous Peoples’ Institution, and community members. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive data analysis model. The findings show that Bakar Batu functions as an egalitarian space for political communication that fosters dialogue, trust, and social legitimacy between the government and indigenous communities. Beyond its cultural and social meanings, the tradition operates as an effective medium of political diplomacy that emphasizes equality, solidarity, and collective participation. This study contributes conceptually by proposing Bakar Batu as a model of political diplomacy rooted in local traditions, offering an alternative approach to inclusive and culturally grounded governance in indigenous regions.